Redesain Gedung SLB/C Kemala Bhayangkari Dengan Pendekatan Arsitektur Inklusif Di Kabupaten Tabanan - I Gst Ayu Agung Rahayu Rimtya Dewi; Ni Wayan Meidayanti Mustika; I Ketut Sugihantara (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
SLB (extraordinary school) is a formal educational institution that serves education for children with special needs. In Tabanan Regency, there is a special school that specializes in educational facilities for people with Tuna Grahita, namely SLB / C Kemala Bhayangkari, which currently has 141 students consisting of 89 male students and 52 female students, and has 10 teachers or educators. This special school has not fulfilled the design according to the SLB standard and is tailored to the needs of mentally retarded children at every level of education. From the results of comparative observations with standard facilities at special schools, seen from the ratio of the number of students in the division of classes and the availability of classrooms, it can be concluded that this SLB / C Kemala Bhayangkari has excess students and still lacks existing space facilities, and the need for physical renovation of buildings, to realize student safety and comfort. The concept of User Responsiveness and Inclusive designs that will be applied adapt to the needs of this facility and make humans the main goal of the design. The design architecture prioritizes user needs, where designs that see the user's condition with their limitations and are designed to ensure user safety and responsive architecture. to the environment / surrounding conditions.